2002
DOI: 10.1046/j.1365-2958.2002.02953.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a partial redundancy of the fibronectin‐binding proteins for the transfer of mycoloyl residues onto the cell wall arabinogalactan termini of Mycobacterium tuberculosis

Abstract: Evidence for a partial redundancy of the fibronectinbinding proteins for the transfer of mycoloyl residues onto the cell wall arabinogalactan termini of Mycobacterium tuberculosis mutant strain of M. tuberculosis restored both the cell wall-linked mycolate defect and the outer cell envelope permeability barrier property. These results are consistent with all three enzymes being involved in cell wall mycoloylation and FbpC playing a more critical role than the others or, alternatively, FbpC is able to compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
81
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 46 publications
2
81
0
1
Order By: Relevance
“…It will be interesting to see whether disruption of this fbp gene completely eliminates TDM in the cell wall of MAR1 and leads to even higher sensitivity to antibiotics. Our in vivo results, in addition to previous reports (5,17,19,30), suggested that FbpA (and probably also FbpB) mycolyltransferase activity preferred trehalose as a substrate, while FbpC prefers arabinogalactan. These preferences may help explain the apparent redundancy of Fbp paralogs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It will be interesting to see whether disruption of this fbp gene completely eliminates TDM in the cell wall of MAR1 and leads to even higher sensitivity to antibiotics. Our in vivo results, in addition to previous reports (5,17,19,30), suggested that FbpA (and probably also FbpB) mycolyltransferase activity preferred trehalose as a substrate, while FbpC prefers arabinogalactan. These preferences may help explain the apparent redundancy of Fbp paralogs.…”
Section: Discussionsupporting
confidence: 81%
“…Curiously, resistance to the limited spectrum of antibiotics tested was unaffected. Genetic analysis showed that all three M. tuberculosis fbp genes could be disrupted individually and that they played partially redundant roles in cell wall biosynthesis (30). The fact that a synthetic analog of a Fbp substrate was able to inhibit growth and cell wall biosynthesis demonstrated that these proteins, or others having similar activities, were essential and thus attractive targets for new antimycobacterial drugs (5).…”
mentioning
confidence: 99%
“…Intriguingly, although both ⌬fbpA and ⌬Msmeg_1529 mutants have comparable defects in FM synthesis, ⌬fbpA is severely defective in biofilm growth. The severity of the ⌬fbpA mutant could be due to possible defect in its cell wall biosynthesis as the gene has been previously implicated in the synthesis of mycolyl esters of cell wall (43,45).…”
Section: Discussionmentioning
confidence: 99%
“…The cord factor has been suggested to be an important determinant for successful infection and survival of MTB within macrophages (Indrigo et al, 2003). Furthermore, it has been shown that 85A and 85B proteins are involved in the covalent attachment of mycolic acids to the mycobacterial cell wall (Puech et al, 2002). Several studies strengthen the hypothesis that differential expression of the antigen 85 genes may be a mechanism utilized by mycobacteria to confuse and evade the host immune system (Armitige et al, 2000;Harth et al, 2002;Ronning et al, 2004).…”
mentioning
confidence: 99%